The Effect of Using Absorbent Carbon on Air Exposed to Air Fresheners on The Histology of The Cornea of The White Rat (Rattus Novergicus) - Yuningtyaswari, Yuningtyaswari; Susanti, Tisa (Green Publisher Indonesia, 2024)
Air freshener contain hazardous chemical such as formaldehyde. Absorbent carbon is used as an adsorbent to reduce air pollution. The goal of this research is to know the use of absorbent carbon to cornea histology on Rattus novergicus that was induced with air freshener. This research was an experimental study with a post-test only control group. The subjects were 28 one-month old male Rattus novergicus Wistar strains divide into 4 groups: Control (K), air freshener (P1), absorbent carbon (P2) and air freshener plus absorbent carbon (P3).The treatment was performed 8 hours/day for 35 days. Data of anterior epithelial thickness were analyzed by One Way Anova test. Data of the overall thickness of the corneal layer and keratocyte number were analyzed by Kruskal Wallis test. The overall thickness of the corneal layer and anterior epithelial thickness showed that there were not significant difference between subject groups (p>0,05). Anterior epithelial thickness showed that there were not significant difference between subject groups (p>0,05). Keratocyte number showed significant difference between subject groups (p<0,05), Mann Whitney test for Keratocyte number showed results P1>P3>K>P2 Absorbent carbon gives postitive effect to reduce cornea damage on Rattus novergicus that induced by air freshener.